Pitavastatin – a new inhibitor of the HMG-CoA reductase: peculiarities of clinical pharmacology and perspectives of its usage in treatment of cardiovascular diseases. - Dzyak, G. V.; Yegorov, K. Yu.; Kolesnik, E. L. (Medicni Perspektivi, 2013)
Cardiovascular mortality makes up 66.3 % of the total mortality in Ukraine. Myocardial infarction, stroke, atherosclerosis of peripheral arteries are the diseases caused by atherosclerosis and are prevalent in the mortality structure. One of the most effective means of successful prevention of cardiovascular disease are drugs that reduce the content of atherogenic lipids in the blood. Statins are the first line drugs for the treatment of patients with dyslipidemia and atherosclerosis in accordance with national and international guidelines. The article presents the features of the pharmacokinetics and pharmacodynamics, results of clinical trials and data on the efficacy and safety of a new inhibitor of the HMG-CoA reductase – pitavastatin (Livazo © (Recordati, Italy). Data from several multicenter randomized studies indicate that pitavastatin significantly reduces the level of cholesterol low-density lipoproteins and triglycerides, significantly increases the level of cholesterol high-density lipoproteins after 12 weeks of observation, and contributes to a significant regression of atherosclerotic plaques. It was shown that pitavastatin has a high level of safety and is well tolerated regardless of patients’ age and racial origin. Pitavastatin is a new effective inhibitor of HMG -CoA reductase, which has been successfully used in many countries for the dyslipidemia treatment in patients with cardiovascular disease, diabetes, kidney diseases and other comorbid conditions.